2018
DOI: 10.1111/jth.14319
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant differences between assays for von Willebrand factor activity

Abstract: It is unclear whether there are differences between von Willebrand factor (VWF) activity assays. We compared the four most used VWF activity assays in 661 von Willebrand disease (VWD) patients. All assays correlated excellently, but a discrepant classification was seen in 20% of patients. Differences between VWF activity assays have a large impact on the classification of VWD. Summary BackgroundMeasuring the ability of von Willebrand factor (VWF) to bind to platelets is crucial for the diagnosis and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Moreover, for different VWF activity assays, we recently reported that they are generally very comparable to each other in patients with type 1 VWD. 34 In conclusion, VWF and FVIII levels after desmopressin administration, which mimic in vivo hemostatic response to hemostatic challenges, are associated with the bleeding phenotype of patients with type 1 VWD. The clinical relevance of this association is highlighted by our findings that patients with the highest VWF and FVIII levels 3 hours after desmopressin administration had a 5-point lower bleeding score, and patients with FVIII:C in the highest quartile had ;10 times lower chance of presenting with an abnormal bleeding score.…”
Section: Vwf:agmentioning
confidence: 91%
“…Moreover, for different VWF activity assays, we recently reported that they are generally very comparable to each other in patients with type 1 VWD. 34 In conclusion, VWF and FVIII levels after desmopressin administration, which mimic in vivo hemostatic response to hemostatic challenges, are associated with the bleeding phenotype of patients with type 1 VWD. The clinical relevance of this association is highlighted by our findings that patients with the highest VWF and FVIII levels 3 hours after desmopressin administration had a 5-point lower bleeding score, and patients with FVIII:C in the highest quartile had ;10 times lower chance of presenting with an abnormal bleeding score.…”
Section: Vwf:agmentioning
confidence: 91%
“…Although not yet widely available, this assay appears to be the most precise tool for measuring VWF activity . A recent report comparing four different VWF activity assays confirmed the precision of VWF:GPIbM; however, it misclassified a significant proportion of genotype 2A, 2B and 3 patients . This assay, and the ristocetin‐dependent VWF:GPIbR, based on a recombinant GPIb fragment captured by a plate‐coated mAb, are insensitive to the VWF variant p.Asp1472His, which results in misleadingly 25% lower VWF:RCo values .…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 99%
“…Due to the fact that the originally developed assay is elaborate and time consuming, has a poor sensitivity and high variation, several new activity tests have been developed in recent years (Bodo et al , ; Boender et al , ). In a recent study, the four currently most widely used VWF activity assays were compared in a cohort of 661 well‐defined VWD patients (Boender et al , ). The assays were found to be highly correlated with each other.…”
Section: Diagnosis Of Severe Vwdmentioning
confidence: 99%
“…The VWF:RCo assay, using ristocetin to activate VWF and whole platelets, was not sensitive enough to classify 18% of the total study population and misclassified half of the genotypically identified 2B patients. Also the VWF:GPIbM test, using gain‐of‐function GPIb fragments that bind spontaneously to VWF, misclassified some definite type 2 and type 3 VWD patients (Boender et al , ).…”
Section: Diagnosis Of Severe Vwdmentioning
confidence: 99%
See 1 more Smart Citation